Arterial stiffness and haemodynamic regulation in adolescent anorexia nervosa versus obesity - Tonhajzerova, Ingrid; Mestanikova, Andrea; Jurko, Alexander; Grendar, Marian; Langer, Peter; Ondrejka, Igor; Jurko, Tomas; Hrtánek, Igor; Cesneková, Dana; Mestanik, Michal (Applied physiology, nutrition, and metabolism, 2020)
Cardiovascular complications contribute to higher morbidity and mortality in patients with anorexia nervosa. We aimed to study biomarkers of cardiovascular risk in anorexic, normal-weight, and obese adolescents with focus on complex cardiovascular autonomic regulation and early arteriosclerotic damage. We examined 20 adolescent girls with anorexia nervosa, 20 obese girls, and 20 healthy normal-weight controls. Collected data: body composition analysis, 5 min recordings of R-R intervals and beat-to-beat blood pressure (BP), and arterial stiffness evaluated using cardio-ankle vascular index (CAVI). Evaluated parameters: beat-to-beat heart rate and BP variability, haemodynamic parameters (total peripheral resistance (TPR) cardiac output), CAVI, and anthropometric indices, including novel body roundness index (BRI). Adolescents with anorexia nervosa had increased CAVI associated with lower arterial constriction indexed by low-frequency band of BP variability compared with normal-weight peers (p = 0.03, p = 0.04, respectively) and obese adolescents (p < 0.01, p = 0.01, respectively). After normalization of CAVI and TPR by BRI, the relationship between CAVI and TPR was significant for all groups with the highest slope in the anorexia nervosa group (R2 = 0.724, p < 0.01). This is the first study revealing early arteriosclerotic damage in anorexic girls with increased CAVI. Complex analysis of cardiovascular autonomic regulation, and early arteriosclerotic, hemodynamic, and anthropometric changes in spectrum anorexia nervosa, normal weight, and obesity could help to understand the mechanisms of increased cardiovascular risk in malnutrition. Novelty Girls with anorexia nervosa showed signs of early arteriosclerotic damage indexed by CAVI. Insufficient sympathetic cardiovascular control was found already in adolescents with anorexia nervosa. The effect of body composition on CAVI was best predicted by novel body roundness index.
Keywords: obezita dětí a dospívajících; Adolescent; Hemodynamics; hemodynamika; Anorexia Nervosa; Child; lidé; Female; mentální anorexie; Cross-Sectional Studies; Vascular Stiffness; dítě; tuhost cévní stěny; mladiství; ženské pohlaví; Pediatric Obesity; průřezové studie; Humans